RELATIONSHIP BETWEEN THE PERCEPTION OF FEMALE ADOLESCENTS ABOUT GINGER WITH THE INTEREST OF DISMENORHEA HANDLING ON HERBAL BASIS AT DHARMA PANCASILA PRIVATE HIGH SCHOOL MEDAN - Krisna, Putri; Sihotang, Monika Rizky; sihaloho, wilfa muslimah; Insani, Septa Dwi; Sitepu, Marlen Sadrina (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2024)
Referring to WHO data, it is known that 1,769,425 women (90%) experience menstrual pain (Dismenorhea). In Indonesia, it is estimated that 55% of women in productive age are tortured by menstrual pain during menstruation (Proverawati, 2017). This study aims to find out the relationship between the perceptions of young adolescents about ginger and their interest about Dismenorhea handling on herbal basis at Dharma Pancasila Private High School Medan in 2019. This study was an analytical study with a cross sectional approach where 57 female adolescents who experienced dysmenorrhea were taken as samples through techniques Proportional Random Sampling. Through the research, the following data were obtained: 41 female adolescents (71.92%) had a positive perception of ginger and 45 adolescent girls (78.9%) had interest in dysmenorrhea treatment on herbal basis. The data were collected through questionnaires which was then processed by the Fisher Exact Test test. Through the research, the value of ρ = 0.025 <0.05 so that it can be concluded that there is a relationship between the perception of the young girls about ginger and interest in dysmenorrhea handling on herbal basis. The health workers are expected to be more active in conducting health counseling so that the perceptions and interests of young women are increasing about the handling of herbal dysmenorhea.